2009
DOI: 10.1007/s00213-008-1443-x
|View full text |Cite
|
Sign up to set email alerts
|

Novice drivers’ performance after different alcohol dosages and placebo in the divided-attention steering simulator (DASS)

Abstract: Rationale The divided-attention steering simulator (DASS) is designed to measure lane-keeping (i.e., a tracking task using a steering wheel) while performing a secondary visual task (responding to digits that appear in the corners of the computer screen). Some studies have already used the DASS, but the magnitude of impairment is difficult to interpret because reference values are lacking. Objective To examine the magnitude of impairment after administration of four different dosages of alcohol and placebo. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 6 publications
1
17
0
1
Order By: Relevance
“…DSs, by removing the influence of driving technique as a confounding factor, provided a valuable opportunity to achieve this goal. Past studies have confirmed that DS systems are a powerful means of evaluating the effect on driving ability of alcohol,15 lack of sleep16 and drug use,17 as well as hemianopia18–20 and other visual field defects 21–26. Moreover, DSs have been found to compare favourably with on-road testing 27…”
Section: Introductionmentioning
confidence: 93%
“…DSs, by removing the influence of driving technique as a confounding factor, provided a valuable opportunity to achieve this goal. Past studies have confirmed that DS systems are a powerful means of evaluating the effect on driving ability of alcohol,15 lack of sleep16 and drug use,17 as well as hemianopia18–20 and other visual field defects 21–26. Moreover, DSs have been found to compare favourably with on-road testing 27…”
Section: Introductionmentioning
confidence: 93%
“…lane exceedance). Alcohol impairs driving performance on each of these measures by increasing SDLP, steering rate, and the number of lane exceedances compared with sober driving performance (Marczinski et al 2008; Fillmore 2007; Harrison and Fillmore 2008; Harrison and Fillmore 2005; Rakauskas et al 2008; Shinar et al 2005; Verster et al 2009). These impairments are typically observed at BrACs at or above 0.08%.…”
Section: Introductionmentioning
confidence: 97%
“…Koelega (1995) concluded that the effects on information processing and divided attention tasks are important because of their relevance to everyday life. Therefore, it is not surprising that alcohol impairs driving and driving-related skills (Holloway 1995; Starmer 1989; Verster et al 2009). The dose–response curve linking blood alcohol level and relative probability of causing a driving accident has long been established and applied in setting legal limits for alcohol levels and driving (Borkenstein et al 1964) with limits in Europe, US and UK currently set around 0.05–0.08% blood alcohol concentration (BAC) levels.…”
Section: Introductionmentioning
confidence: 99%